Development of an fMRI-compatible driving simulator with simultaneous measurement of physiological and kinematic signals: The multi-biosignal measurement system for driving (MMSD) - Kim, Hyung-Sik; Mun, Kyung-Ryoul; Choi, Mi-Hyun; Chung, Soon-Cheol (IOS PRESS, 2020)
BACKGROUND: A system that comprehensively analyzes a complex perceptual-motor behavior such as driving, by measuring changes in the central and autonomic nervous systems integrated with measurement of changes in vehicle operation, is lacking. OBJECTIVE: We aimed to develop a functional magnetic resonance imaging (fMRI)-compatible driving simulator to enable simultaneous measurement of physiological, kinematic, and brain activations. METHODS: The system mainly comprises a driving simulator and physiological/kinematic measurement. The driving simulator comprises a steering wheel, an accelerator, a brake pedal, and a virtual-reality optical system. The physiological system comprises a skin-conductance-level and a photoplethysmographic meter. The kinematic system comprises a 3-axis accelerometer and a 2-axis gyroscope attached to the accelerator foot. To evaluate the influence of the MR system on the MMSD, physiological and kinematic signals were measured. RESULTS: The system did not blur or deform the MR image. Moreover, the main magnetic field, the gradient magnetic field, and the RF pulse of the MR system did not introduce noise into the physiological or kinematic signals. CONCLUSION: This system can enable a comprehensive evaluation of cognitively complex behaviors such as driving, by quantitatively measuring and analyzing concurrent brain activity, autonomic nervous system activity, and human movement during simulated driving.
Keywords: DISTRACTION TASK; PERFORMANCE; ALCOHOL; SPEED